Analysis of Phenolic and Flavonoid Content, α-Amylase Inhibitory and Free Radical Scavenging Activities of Some Medicinal Plants. (3rd October 2022) - Pandey, Lalit Kala; Sharma, Khaga Raj
Abstract : In Nepal, about 700 plant species have been reported to be used for the primary care of different diseases. However, many of them have not been studied yet for their scientific evidence. The main aim of this study is the quantitative analysis of flavonoids and phenolic content, antioxidant, and antidiabetic activities of the extracts of four different medicinal plants, namely, Pogostemon benghalensis, Aleuritopteris bicolor, Crateva unilocularis, and Rungia pectinata growing in Nepal. The methanol extracts of plant samples were prepared by the hot percolation method using the Soxhlet apparatus. The phytochemicals of the plant extracts were analysed by colour differentiation methods using different analytical reagents. The phenolic content was estimated by using Folin–Ciocalteu's phenol reagent and the flavonoid was estimated by the aluminium chloride colorimetric method. The 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging assay was used to evaluate the antioxidant potential. The α -amylase enzyme inhibition activity was performed to evaluate the antidiabetic activity of plant extracts. The amount of total phenolics and flavonoids content was found to be the highest in Pogostemon benghalensis (169.43 ± 3.58 mg GAE/g and 65.2 ± 2.0 mg QE/g), respectively, which also showed the most potent free radical scavenging activity (IC50 35.92 ± 0.65  μ g/mL). The extract of Aleuritopteris bicolor showed the highest α -amylase inhibitory activity (IC50 651.58 ± 10.32  μ g/mL) whereas Crateva unilocularis and Pogostemon benghalensis exhibited moderate activity. The extract of Rungia pectinata showed the least activity towards α -amylase inhibition. Some of the medicinal plants selected in this study showed high TPC and TFC values with potent biological activities. To the best of our knowledge, these medicinal plants have the least exposure to their biological activities, and the results provide scientific evidence for the traditional uses of these plants against diabetes and infectious diseases. However, a detailed study can be performed in these plants to isolate the active chemical compounds and to evaluate in vivo pharmacological activities to know the active drug candidates for the future drug development process.